2011
DOI: 10.1093/ndt/gfr039
|View full text |Cite
|
Sign up to set email alerts
|

Daily peritoneal administration of sodium pyrophosphate in a dialysis solution prevents the development of vascular calcification in a mouse model of uraemia

Abstract: Our findings suggest potential for PPi, administered during PD, to prevent the development of VC and to potentially extend the life of ESRD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…The high prevalence of vascular calcification in chronic kidney disease patients on dialysis is associated with reduced plasma PP i levels, 53 and recent findings in mice suggest that vascular calcification might be prevented by inclusion of PP i in dialysis solutions. 73 In mice lacking functional ANK, there is intracellular trapping of PP i and reduced levels of extracellular PP i , which leads to ectopic mineralization in many locations. 41 Interestingly, vascular mineralization does not occur in Ank -/-mice, suggesting that there is sufficient ENPP1-mediated generation of PP i to prevent ectopic calcification in vessel walls.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of vascular calcification in chronic kidney disease patients on dialysis is associated with reduced plasma PP i levels, 53 and recent findings in mice suggest that vascular calcification might be prevented by inclusion of PP i in dialysis solutions. 73 In mice lacking functional ANK, there is intracellular trapping of PP i and reduced levels of extracellular PP i , which leads to ectopic mineralization in many locations. 41 Interestingly, vascular mineralization does not occur in Ank -/-mice, suggesting that there is sufficient ENPP1-mediated generation of PP i to prevent ectopic calcification in vessel walls.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of chronic uremia, diminished circulating concentrations of PPi are paralleled by an increase of TNAP acitivity [129,130,131,132,133]. Recent studies with uremic rats indicate that administration of PPi is able to revert this mechanism and to prevent vascular calcification [134,135]. …”
Section: Calcification Inhibitorsmentioning
confidence: 99%
“…In our previous animal study, we showed that PPi was able to prevent the progression of VC when PPi was administrated by the intraperitoneal route, simulating a peritoneal dialysis delivery, and immediately after the creation of CKD [13]. Since these studies demonstrated robust efficacy of PPi therapy on VC that was probably harmless regarding the bone [16], and since human patients treatment is likely justified only after the establishment of VC, we sought here for the first time to determine if such a treatment is able to block or reverse the progression of established VC.…”
Section: Introductionmentioning
confidence: 98%
“…Two experimental studies were conducted recently to explore this possibility. In these ''prevention'' studies, O'Neill et al [12] and our group [13] administered PPi via the subcutaneous or the peritoneal route to rats or mice with CKD, i.e., over 1 and 2 months, respectively. The studies showed that long-term PPi treatment was able to slow and even to halt the progression of VC in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%